Single-carrier phase-disposition PWM techniques for multiple interleaved voltage-source converter legs - Konstantinou, Georgios (2020)
Interleaved converter legs are typically modulated with individual carriers per leg and phase-shifted pulse width modulation (PS-PWM) as it facilitates current balancing amongst the legs. Phase-disposition PWM (PD-PWM), despite the better harmonic performance, cannot be directly used due to the resulting current imbalance that may damage the converter. This paper addresses the current sharing issue and proposes a sorting algorithm implementation that enables single-carrier PD-PWM technique for interleaved two-level converter legs. An extension of the proposed algorithm through a switching state feedback loop, limiting the average switching frequency, is also developed. In both cases, the output current is of high quality and shared amongst the phase-legs, while the deviation between the phase-leg currents is well regulated. Simulation results demonstrate the general function of method for multiple interleaved legs as well as its current sharing capabilities for high-power applications. Experimental results from a low-power laboratory prototype validate the operation of the proposed approach.